2020
DOI: 10.1080/01490419.2020.1771486
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Measurements along Commercial Ferry Lines in the Baltic Sea and Their Use for Geodetic Purposes

Abstract: In 2017 and 2018 GFZ performed two gravimetry campaigns on commercial ferries in the Baltic Sea.The nature of such "non-dedicated" campaigns is different from "dedicated" campaigns that are performed on research vessels with tracks planned according to gravity measurement needs. The nondedicated campaigns use non-survey vessels or survey vessels running for other purposes such as hydrographic measurements, which may require additional corrections. To assess the usefulness of non-dedicated campaigns, we analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Offshore, BSCD2000 will be realized through GNSS and high-resolution (0.01 × 0.02 arc-deg) geoid modeling, while onshore, BSCD2000 will be compatible with the national height system realizations of the Baltic Sea countries (e.g., EH2000, N2000, and RH 2000) and will coincide with national geoid models to allow seamless height transitions (this will be achieved through the blending of the models, developed by different geoid computation centers [50]). For this purpose, the Baltic Sea is being densely covered by ship-and airborne marine gravity data [24,[51][52][53][54][55] to allow high-accuracy marine geoid modeling. Note that since the provided discussion is limited to the Estonian, Finnish, and Swedish height system realizations, an interested reader is encouraged to read additional details concerning BSCD2000 and the other Baltic Sea countries from [34,49,50].…”
Section: Baltic Sea Chart Datum 2000mentioning
confidence: 99%
“…Offshore, BSCD2000 will be realized through GNSS and high-resolution (0.01 × 0.02 arc-deg) geoid modeling, while onshore, BSCD2000 will be compatible with the national height system realizations of the Baltic Sea countries (e.g., EH2000, N2000, and RH 2000) and will coincide with national geoid models to allow seamless height transitions (this will be achieved through the blending of the models, developed by different geoid computation centers [50]). For this purpose, the Baltic Sea is being densely covered by ship-and airborne marine gravity data [24,[51][52][53][54][55] to allow high-accuracy marine geoid modeling. Note that since the provided discussion is limited to the Estonian, Finnish, and Swedish height system realizations, an interested reader is encouraged to read additional details concerning BSCD2000 and the other Baltic Sea countries from [34,49,50].…”
Section: Baltic Sea Chart Datum 2000mentioning
confidence: 99%
“…With the updated gravimeter Chekan-AM, the drift in the campaign DENEB2017 was very stable with a normal value of 0.50 mGal/day, as shown in Figure 3c. Furthermore, the gravimetry measurements of the campaign URD2017 (also another campaign Finnlady2018) implemented on ferries also had a very stable drift [47,48].…”
Section: Drift Improvementmentioning
confidence: 99%
“…After the gravimeter Chekan-AM was updated, the first campaign of DENEB2017 showed significant improvements: The absolute values of Min (−0.76 mGal) and Max (0.52 mGal) of gravity differences at crossover points were within 1.00 mGal, and the RMS value reached 0.30 mGal, which is close to the current claimed the highest precision of 0.10-0.20 mGal. In addition, the gravimetry measurements of the campaign URD2017 (also another campaign Finnlady2018) implemented on ferries were at the precision level of 1.00 mGal along the tracks [47,48].…”
Section: Crossover Points Checkingmentioning
confidence: 99%
“…In most dynamic gravimetry campaigns, horizontally stabilised spring-type gravimeters have been installed, e.g. Nettleton et al (1960), Brozena et al (1997), Forsberg and Olesen (2010), Lu et al (2017) and Ince et al (2020). Since the 1990s, the use of inertial measurement units (IMUs) strapped-down to the moving vehicle became more and more convenient as it was shown that the accuracy is comparable to that of spring type gravimeters (Glennie et al 2000;Becker et al 2015;Johann et al 2020;Yuan et al 2020).…”
Section: Dynamic Gravimetrymentioning
confidence: 99%